2013
DOI: 10.1002/dta.1587
|View full text |Cite
|
Sign up to set email alerts
|

PPARgamma agonist pioglitazone does not enhance performance in mice

Abstract: Peroxisome-proliferator-activated receptor (PPAR) delta and adenosine monophosphate (AMP)-activated protein kinases (AMPKs) regulate the metabolic and contractile characteristics of myofibres. PPAR proteins are nuclear receptors that function as transcription factors and regulate the expression of multiple genes. AMPK has been described as a master metabolic regulator which also controls gene expression through the direct phosphorylation of some nuclear proteins. Since it was discovered that both PPARdelta ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…3 Experiments were approved under NYU-IACUC protocol IA16-01021. Mice underwent two separate treadmill running protocols adapted from [11][12][13] : (i) 3 weeks of running before first tamoxifen (TAM) injection and then three additional weeks of running (total 6 weeks of exercise; Supplementary material online,…”
Section: Exercise Protocol In Micementioning
confidence: 99%
“…3 Experiments were approved under NYU-IACUC protocol IA16-01021. Mice underwent two separate treadmill running protocols adapted from [11][12][13] : (i) 3 weeks of running before first tamoxifen (TAM) injection and then three additional weeks of running (total 6 weeks of exercise; Supplementary material online,…”
Section: Exercise Protocol In Micementioning
confidence: 99%
“…CMS induced a decrease in locomotor activity indicated a depressive state of animals because of a loss of interest for the movement, or for exploring the environment. Pioglitazone increased spontaneous motor activity in the CMS-exposed mice, without effect on locomotor activity in normal mice [ 38 ]. Gavage administration of pioglitazone was effective at the 2.5 and 5.0 mg/kg doses for ameliorating the symptoms of depression, but the 2.5 mg/kg dosage was more effective.…”
Section: Discussionmentioning
confidence: 99%
“…Pioglitazone, in contrast to training alone, did not enhance maximal aerobic velocity, endurance capacity, and grip strength. Furthermore, expression of mitochondrial biogenesis markers, such as PGC-1a and citrate synthase activity in the soleus muscle, were not changed after pioglitazone treatment of mice [75]. In contrast, a clinical study showed that rosiglitazone (4 mg daily for a period of 4 months) increased maximal exercise capacity in individuals with type 2 diabetes.…”
Section: Thiazolidinedionesmentioning
confidence: 89%